2004
DOI: 10.12968/jowc.2004.13.1.26563
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled study of four-layer compression versus Unna’s Boot for venous ulcers

Abstract: Profore is as effective as Unna's Boot in the treatment of venous leg ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 4 publications
0
49
0
Order By: Relevance
“…[20] after 12 weeks of observation achieved 74% healing of large ulcerations (the initial average area was 15.4 cm 2 ) which had been treated ineffectively before using one-layer elastic bandages. The results of the next research [21-23] showed lower, but satisfactory rates. It was suggested that four-layer compression is as effective as two-layer (short-stretch) compression.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[20] after 12 weeks of observation achieved 74% healing of large ulcerations (the initial average area was 15.4 cm 2 ) which had been treated ineffectively before using one-layer elastic bandages. The results of the next research [21-23] showed lower, but satisfactory rates. It was suggested that four-layer compression is as effective as two-layer (short-stretch) compression.…”
Section: Discussionmentioning
confidence: 94%
“…In some of the research we can notice the superiority of multi-layer systems over one-layer compression [18-20]. In other research, the effectiveness of the investigated methods was found comparable and the differences statistically insignificant [2, 21-23]. Extensive research comparing the effectiveness of multi-layer systems with short-stretch compression did not show statistically relevant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short stretch compression (inelastic) and Unna's boot was found to support the pump function better than a long stretch compression (elastic)[1920] (evidence level A).…”
Section: Head To Head Comparison Between Various Modalities Of Comprementioning
confidence: 99%
“…However, the consistent pressure of bandaging has been a long-term problem. Healing outcomes were found to vary widely (HT = 40–138 days; HR = 51–93%) [18, 22, 23]. Studies have been unable to demonstrate the superiority of multi-layer bandage compression over other types [24, 25].…”
Section: Introductionmentioning
confidence: 99%